House improvements and community participation in the control of Triatoma dimidiata re-infestation in Jutiapa, Guatemala Melhorias habitacionais com participação comunitária no controle da re-infestação por Triatoma dimidiata em Jutiapa, Guatemala - Carlota Monroy; Dulce Maria Bustamante; Sandy Pineda; Antonieta Rodas; Xochitl Castro; Virgilio Ayala; Javier Quiñónes; Bárbara Moguel (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
The deterioration or absence of plaster walls in houses and poor hygienic conditions are the most important risk factors for indoor Triatoma dimidiata infestation in Guatemala. A cross-disciplinary study was conducted addressing T. dimidiata infestation, household hygiene, and housing construction. The study focused on local materials and cultural aspects (including gender roles) that could lead to long-term improvements in wall construction. A new plaster mix for walls was developed on the basis of laboratory studies on construction materials recommended by local villagers. Four villages with persistent (post-spraying) T. dimidiata infestation were studied. In two villages, an ecosystem approach was implemented, and the homeowners conducted wall improvements and household sanitation with the support of the interdisciplinary team (the ecosystem intervention). In the other two villages, a vector control approach based on insecticide spraying was adopted (traditional intervention). Both interventions were associated with a reduction in T. dimidiata infestation, but only the ecosystem approach produced important housing improvements (sanitation and wall construction) capable of preventing T. dimidiata re-infestation in the long term. A degradação ou ausência de reboco nas paredes e as condições higiênicas deficientes são os fatores de risco mais importantes para a infestação intradomiciliar por Triatoma dimidiata na Guatemala. Realizamos um estudo transdisciplinar sobre infestação por T. dimidiata, higiene intradomiciliar e condições de construção. O estudo destacou as questões de materiais locais e aspectos culturais (inclusive papéis de gênero) que poderiam levar a melhorias nas condições das paredes no longo prazo. Formulou-se uma nova mistura de gesso para paredes, após estudos de laboratório sobre materiais de construção com base em recomendações dos residentes locais. Foram estudados quatro vilarejos com infestação por T. dimidiata que havia persistido mesmo após aplicação de inseticida. Em duas comunidades, foi implementada uma abordagem ecossistêmica, e os residentes implementaram melhorias nas paredes e no saneamento domiciliar, com o apoio da equipe interdisciplinar (intervenção ecossistêmica). Nas duas outras comunidades, adotou-se uma estratégia de controle com base na aplicação de inseticida (intervenção tradicional). Ambas as intervenções levaram a uma redução na infestação por T. dimidiata, mas apenas a abordagem ecossistêmica produziu melhorias importantes nas condições de moradia (saneamento e revestimento das paredes) capazes de prevenir a re-infestação por T. dimidiata no longo prazo.